Republic of Kazakhstan : Country Procurement Assessment Report - World Bank (Washington, DC, 2013)
This Country Procurement Assessment Report (CPAR) is the first such report carried out for the Republic of Kazakhstan. It is based on an extensive review, qualitative analysis and discussion on the procurement environment in the Republic of Kazakhstan. The report includes: (i) the compatibility or otherwise of the national public procurement regime with the Bank's Procurement Guidelines; (ii) past performance in administration of procurement process under the Bank supported operations; (iii) a general assessment of legal, institutional and other risks associated with the public procurement in the country; (iv) impact of various other regulatory regimes (e.g. foreign exchange, taxation and banking system etc.), on public procurement; (v) an assessment of current commercial procurement practices; and (vi) effectiveness of existing accountability and anti corruption framework. The report is organized in two volumes and a set of annexes. Volume I presents the summary of findings and recommendations, and the agreed action plan. Volume II contains factual material, analysis and discussions of procurement environment in the country.